2019
DOI: 10.1021/acssuschemeng.9b02044
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency and Thermally Sustainable Perovskite Solar Cells with Sandpaper-Aided Flexible Haze/Antireflective Films

Abstract: A sandpaper-aided haze film (SAHF) is fabricated by a single-step, facile, and cost-effective soft-imprint lithography technique via commercially available and inexpensive sandpaper master molds. Such a low-priced SAHF exhibited a superior antireflective ability with an average transmittance of 93.7% in the wavelength range of 350–800 nm. It also possesses a high diffuse transmittance and very high haze transmission values of approximately 84.3% and 89.8%, respectively. Resultantly, laminating the SAHF on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…10k‐PDMS showed the lowest reflectance of ≤ 4%, while 2k‐ and 6k‐PDMS were ≤ 5%. [ 64,65 ] The high transmittance and low reflectance enable suppressed light loss and enough light utilization to improve OPV efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…10k‐PDMS showed the lowest reflectance of ≤ 4%, while 2k‐ and 6k‐PDMS were ≤ 5%. [ 64,65 ] The high transmittance and low reflectance enable suppressed light loss and enough light utilization to improve OPV efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The lower the haze value, the higher the clarity of the NP film. The haze value can be obtained by the following relation normalh normala normalz normale false( % false) = ( T 4 T 2 T 3 T 1 ) × 100 where T 1 and T 2 are the incident light and the total transmittance of the NP film, respectively, T 3 is the light scattered inside the integrating sphere, and T 4 is the light scattered by the NP film in addition to that inside the integrating sphere . The haze values of the NP films were obtained using a haze meter (Nippon Denshoku Co., NDH-5000).…”
Section: Resultsmentioning
confidence: 99%
“…A strong correlation was observed where T 1 and T 2 are the incident light and the total transmittance of the NP film, respectively, T 3 is the light scattered inside the integrating sphere, and T 4 is the light scattered by the NP film in addition to that inside the integrating sphere. 44 The haze values of the NP films were obtained using a haze meter (Nippon Denshoku Co., NDH-5000). The obtained haze values were about 2−3%, indicating weak light scattering (Figure 5b).…”
Section: Structural and Optical Responses Of Ito Npsmentioning
confidence: 99%
“…The development of transparent electrodes contributes to the realization of semitransparent f-PSCs, which are promising to work in smart displays and windows. Jang et al reported semitransparent f-PSCs with both transparent electrodes fabricated by graphene doping with bis­(trifluoromethanesulfonyl)­amide (TFSA) and triethylenetetramine (TETA), which realized PCEs of 10.56 and 10.73% at two sides, respectively . The research on all-inorganic f-PSCs is conducive to solving the stability problem owing to their good thermal and illumination stabilities. Lead-free f-PSCs can reduce the heavy metal pollution of lead. An adjustable band gap makes f-PSCs applicable in tandem solar cells. Additionally, a series of low-cost, environmentally friendly, and biocompatible materials have been employed in f-PSCs. Undoubtedly, these investigations will facilitate the commercial applications of f-PSCs.…”
Section: Applications Of F-pscsmentioning
confidence: 99%